Comparison of two uncoupled ductile damage initiation models applied to DP900 steel sheet under various loading paths. (January 2021) - Tuo, Zhiyu; Yue, Zhenming; Zhuang, Xincun; Min, Xinrui; Badreddine, Houssem; Qiu, Liangyu; Gao, Jun
Accurate prediction of the fracture occurrence of high strength materials is always the hot spot in the research field of metal-forming process. Appropriate material model is the key issue which can accurately describe the mechanical forming behavior under different forming conditions. However, advanced fully coupled damage/behavior models are heavy to use by engineers and have a high cost in term of calculation consuming time. In this paper, a simple uncoupled damage approach, designed to be easy to use for engineers and accurate as well, is investigated. Two uncoupled damage models, which consider the effect of the Lode angle and the hydrostatic pressure, combing three typical hardening rules, are selected and applied to the damage prediction of DP900 dual-phase steel. The hardening properties and forming limit strains under different loading paths of DP900 are investigated and studied throughout a variety of mechanical experiments, including the uniaxial tensile test, the pre-notched tensile tests with three notched radii, and the butterfly tests. Finally, the prediction accuracy of the used models for DP900 is compared and discussed.